PEMANFAATAN WORTEL AFKIR (DAUCUS CAROTA L.) SEBAGAI BAHAN UTAMA PEMBUATAN PUPUK ORGANIK CAIR (POC) - Agus Susanto Ginting; Sumatera Tarigan; Risman Halawa; Nikolas Jovi Tarigan (JURNAL AGROTEKNOSAINS, 2023)
Karo regency is center for carrot (Daucus carota L.) production in North Sumatra. It is estimated more than 1% of the rejected carrot yields are produced in each planting period. With the predicted harvest area, more than 1,000 tons of rejected carrots will be produced annually. This potential can be used as the material for the manufacture of liquid organic fertilizer (LOF). There are three research variables that were carried out, namely: 1) Independent variables consisting of fermentation periode consisting of 10 days, 20 days, 30 days and 40 days. 2) Fixed variable consisting of 4 kg of rejected carrots, 5 liters of water, 5 liters of old coconut water, 0.6 liters of brown sugar water, 0.05 kg of yeast, 0.5 liters of EM-4. 3) Bond variables consist of C-Organic content, Phosphorus content, Potassium content  and Nitrogen and pH content. The results showed that the peak of microorganism activity occurred on the 30th day. This treatment obtained the highest proportions of 0.07%, 0.14%, 0.87%  for Nitrogen, Phosphorus and Potassium levels respectively. The highest C-Organic content was obtained in the H-20 and H-30 treatments with a proportion of 1.55%. The acidity level was stable at a value range of 3.5 from the start to the end of the quenching process. LOF carrots produced are still not in accordance with established quality standards. The percentage value of macro elements, C-Organic and pH is still below the set quality standards.